2017
DOI: 10.1002/elan.201700155
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Immunosensors for the Rapid Screening of Cystic Fibrosis and Duchenne Muscular Dystrophy

Abstract: Cystic Fibrosis (CF) and Duchenne Muscular Dystrophy (DMD) are well characterized progressive inherited diseases associated with significant morbidity and mortality. Therefore, the early, rapid and affordable diagnosis of these disorders through newborn screening is highly important for the appropriate management. Here, we report label‐free impedance immunosensors for the simple screening of CF and DMD through the detection of cystic fibrosis transmembrane conductance regulator (CFTR) protein fragment and a pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…After the incubation with cysteamine (red curve), an increase in the peak current and a decrease in the ΔE was observed indicating the success of the self assembly of the cysteamine on the electrode surface. The terminal amine groups of the cysteamine show a positive charge which attracts the redox anions from the solution causing enhancement of the electron transfer rate .…”
Section: Resultsmentioning
confidence: 99%
“…After the incubation with cysteamine (red curve), an increase in the peak current and a decrease in the ΔE was observed indicating the success of the self assembly of the cysteamine on the electrode surface. The terminal amine groups of the cysteamine show a positive charge which attracts the redox anions from the solution causing enhancement of the electron transfer rate .…”
Section: Resultsmentioning
confidence: 99%
“…While the classical presentation of CF is well known, a definitive CF diagnosis is only achieved by a combination of symptoms, family history, a positive newborn screening test, and laboratory evidence of CFTR malfunction, e.g ., positive genetic testing for two CFTR mutations (one in each parental gene) or elevated sweat sodium chloride levels. ,, Novel biosensor-based approaches have suggested that the level of the soluble form of CFTR protein may be used as a diagnostic marker for CF in newborns using dried blood spots …”
Section: Introductionmentioning
confidence: 99%
“…3,4,8−11 Novel biosensor-based approaches have suggested that the level of the soluble form of CFTR protein may be used as a diagnostic marker for CF in newborns using dried blood spots. 12 Currently, there is no cure for CF. Therapies that correct CFTR function are promising but still not sufficiently available to patients.…”
Section: Introductionmentioning
confidence: 99%